Soybean Genotype Ds 3108 Identified As Potential Donors for Major Insect Pest and Disease Resistance - S. K. Lal; A. Talukdar; A. Rajenderan; M. Saini; Archana Anokhe; B.P. Mallikarjuna; J.B. Singh; K.P. Singh; Sunil Kumar Singh; Anchal Dass; Anirban Roy; Govindsamy (Annals of Agricultural Research, 2023)
The soybean [Glycine max (L.) Merrill] is a nutrient rich & economically important crop. Soybean is affected by many pest and disease complexes, which results in significant yield reduction. DS 3108 was evaluated in plant breeding, entomological, pathological and agronomic trials for three consecutive years in All Indian Co-ordinated Research project on Soybean over multiple locations. It was tested in north eastern hill zone for three years. Based on three years data over multiple locations genotype DS 3108 has been identified as a potential donor for high yield and resistance traits. It showed considerable tolerance against Mung bean yellow mosaic virus, whitefly infestation, and stem-tunnelling by stem fly and damage by defoliators. Genotype (DS 3108) recorded 4.1% tunnelling due to stem fly as against 14.6% in susceptible check (JS 335). From the three year screening it was confirmed that DS 3108 has shown highly resistant reaction against Pod blight, Rhizoctonia aerial blight, Phakapsora pachirizi, Mungbean yellow mosaic virus, Bacterial leaf blight, Collar Rot and for Bacterial leaf blight from all the three location i.e. Medziphema, Jorhat and Bisnath Chariali. It was also found resistant to majority of insect as compared to other test entries which showed susceptible to slightly resistant reactions. In case of Bihar hairy caterpillar infestation DS 3108 has shown lowest damage i.e. 10.98 and 2.82 in the consecutive two year (2018, 2019) and has been demarcated under moderately resistant whereas susceptible check has shown highest damage i.e. 11.66 and 4.68 in the same two consecutive years. In the Agronomy trial (2019), DS 3108 has out yielded all the three checks in both the row spacing (30cm and 45cm) experiments. It has yielded 2193 kg/ha which is 11% increase in grain yield over the susceptible check JS 335 and 25% yield enhancement over DSb -32.